2019
DOI: 10.1038/s41598-019-53472-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure of Patient and Operating Room Personnel by Fluoroscopy and Navigation during Spinal Surgery

Abstract: Intraoperative radiography imaging is essential for accurate spinal implant placement. Hazards caused by ionizing radiation raised concern on personnel’s work life long exposure in the operating room (OR). To particularize a cumulative risk estimation of radiation of personnel and patient, depending on used methods (C-arm fluoroscopy, O-arm navigation) and patient characteristics during spinal surgery, detailed investigation of radiation exposure in a clinical setting is required. Lumbosacral dorsal spinal fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 15 publications
(12 reference statements)
1
43
1
3
Order By: Relevance
“…For spatial scales s of 2 to 8, high errors above 10% occurred mostly outside of the primary X-ray, while for s = 16, the overall error distributions indicate a systematic trend. Figure 6 shows plots of the relative error and runtime performance measures of our method for a reduced number of simulated primary particles ranging from 1×10 6 to 1×10 8 for different scales s. Note that for 1 × 10 7 and 1 × 10 8 particles, the error increased with increasing the spatial scale s, while for fewer particles, the error decreased again with s = 8 and higher.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For spatial scales s of 2 to 8, high errors above 10% occurred mostly outside of the primary X-ray, while for s = 16, the overall error distributions indicate a systematic trend. Figure 6 shows plots of the relative error and runtime performance measures of our method for a reduced number of simulated primary particles ranging from 1×10 6 to 1×10 8 for different scales s. Note that for 1 × 10 7 and 1 × 10 8 particles, the error increased with increasing the spatial scale s, while for fewer particles, the error decreased again with s = 8 and higher.…”
Section: Resultsmentioning
confidence: 99%
“…While diagnostic reference levels [4] serve as a guidance for the expected overall exposure of the patient, it is difficult to draw conclusions on organ dose levels from them. However, for complicated FGIs, e.g., neuro-interventional procedures, repeatedly acquired digital subtraction angiography acquisitions, cone-beam CT reconstructions, and biplane imaging can lead to high dose values [5][6][7][8][9]. They may cause DNA damage [10] or cataract [11].…”
Section: Introductionmentioning
confidence: 99%
“…CT‐based navigation systems (including robotic guidance systems) allow the surgery to proceed without much additional intraoperative fluoroscopy and may critically reduce the cumulative radiation dose received by surgeons 11 ,. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated significantly decreased radiation exposure to the surgeon in the navigation cohort compared to the fluoroscopy cohort. They concluded that a spinal surgeon using navigation could perform up to 10 times the number of surgeries until maximum permissible annual effective radiation dose would be reached compared to fluoroscopy 14 . Although several studies have evaluated radiation burden during fluoroscopic‐guided and CT‐navigated spinal surgeries, detailed comparisons between fluoroscopic and robotic guidance are lacking 14 ,.…”
Section: Discussionmentioning
confidence: 99%
“…der Komplikationen oder der Revisionsraten aufgrund einer Fehllage (Penetration) der Pedikelschrauben [4,17,18]. Da bei der CT-gestützten Navigation (CAN = auf Englisch: CT-assisted navigation) während des CT-Scans ein Verlassen des Operationssaals für Operateure und Personal möglich ist, sind diese kaum einer Strahlenexposition ausgesetzt [19]. Allerdings ist die fluoroskopisch gestützte Navigation (FAN = auf Englisch: fluoroscopic-assisted navigation) mit einer Strahlenexposition für den Operateur verbunden, da dieser bei der fluoroskopisch gestützten Implantation der Pedikelschrauben direkt am Patienten steht [20].…”
Section: Navigationsgestützte Operationsverfahrenunclassified